The Performance of SHS Learners in Writing Scholarly Research with the Aid of Instructional Scaffolding - Martinez, Vanneza Clare (JPAIR Multidisciplinary Research, 2019)
A research paper is widely considered an important requirement produced by learners. However, writing a research paper has been a common challenge for most Senior High School learners. In the Philippines, most Senior High School learners have difficulty in explicating their contentions in their study due to their lack of knowledge in conducting and writing a research paper. One of their problems is applying the academic writing conventions such as formality in writing, coherence, grammar, and other related skills involved in writing conventions in writing a scholarly paper. Hence, this study aims to enhance learners’ research writing skills by utilizing Instructional Scaffolding as a teaching technique that provides support systems, like reinforcements or relevant activities in molding independent learners, until it becomes unnecessary for them. This quantitative study determined the effectiveness of Instructional Scaffolding by applying correction symbols as an intervention on the difficulties experienced by the Senior High School grade 12 STEM learners in writing a research paper. Twenty-five research papers were investigated by analyzing them with the checklist used by Erel and Bulut (2007), which was also subjected to the T-test formula. The results of this study revealed a decrease in Mean error scores from 75.52 to 20.52, which indicates a significant improvement in the learners’ writings of learners in their research paper. This result implied that instructional scaffolding enhanced the writing competence of learners in writing a research paper.